DOI: 10.18130/v33g1f
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Appropriate Self-Management Program for Hispanic Adults with Type 2 Diabetes and Low Health Literacy Skills

Abstract: AcknowledgmentsI would like to acknowledge the members of this capstone committee for their guidance and support during the project. I am indebted, in particular, to the chair of the committee and academic advisor, Professor Ann Gill Taylor, for the innumerable hours given throughout each phase of the project to ensure the success of this endeavor. To her and to the rest of the GEM investigators I am grateful for the opportunity to have been a part of their team, which offered a unique learning experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Time management was mentioned more as a barrier to do physical activity than eating healthily. Difficulties in finding time, stress and fatigue after long working hours were also frequently mentioned as barriers to physical activity (Brunk et al 2017;Ide et al 2018;Kaltman et al 2015;Korkiakangas et al 2011;Lawton et al 2006). This is further supported by a study by Umeh and Nkombua (2018), they found that the barriers to engage in exercise include not having the time (43.9%), not having companions (19.4%), stress (16.3%), and bad climate (10.2%).…”
Section: Extrinsic Barriers To Make Lifestyle Changesmentioning
confidence: 84%
See 4 more Smart Citations
“…Time management was mentioned more as a barrier to do physical activity than eating healthily. Difficulties in finding time, stress and fatigue after long working hours were also frequently mentioned as barriers to physical activity (Brunk et al 2017;Ide et al 2018;Kaltman et al 2015;Korkiakangas et al 2011;Lawton et al 2006). This is further supported by a study by Umeh and Nkombua (2018), they found that the barriers to engage in exercise include not having the time (43.9%), not having companions (19.4%), stress (16.3%), and bad climate (10.2%).…”
Section: Extrinsic Barriers To Make Lifestyle Changesmentioning
confidence: 84%
“…Patient's food habit Five qualitative studies mentioned about food habit as a barrier against following a diabetic diet (Brunk et al 2017;Chary et al 2012;Ide et al 2018;Mansyur et al 2015;Mathew et al 2012;Sapkota et al 2017;Savoca & Miller 2001). Participants clarified that it was very hard to change their eating habit as they had been used to it since they were small (Ide et al 2018).…”
Section: Main Themesmentioning
confidence: 99%
See 3 more Smart Citations